Menilai Kepuasan Pengguna Dalam Sistem Informasi Pendaftaran Menggunakan Framework PIECES - Mutia Herman; Muhammad Irwan Padli Nasution (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Assessing user satisfaction is important as a benchmark for assessing the quality and effectiveness of information systems used in public Services. Initial observations at the North Sumatra Provincial Library and Archives Office found indications of difficulties in accessing the website, slow system response, unclear Service information, lack of digital Service promotion, and less attractive interface display. This study aims to measure the level of user satisfaction with the registration information system of the North Sumatra Provincial Library and Archives Office using the PIECES framework which includes aspects of performance, Information and Data, Economics, control and securit, Efficiency, and Service. The research method used descriptive quantitative through the distribution of questionnaires with a total of 14 participating respondents. The results showed that the user satisfaction level score for each variable was 3.89; Information and Data 3.92; economy 4.48; control and safety 3.82; Efficiency 4.16; and Services 2.78. The achievement of high satisfaction in the Economics aspect shows that the system provides benefits of saving time and user costs. However, the Service aspect with the lowest achievement indicates that there are still limitations in the quality of the interface and Service support to users. This research contributes as a material for system evaluation and the basis for improving registration information system Services in related agencies.